2016
DOI: 10.1098/rspa.2016.0682
|View full text |Cite
|
Sign up to set email alerts
|

Self-locking degree-4 vertex origami structures

Abstract: A generic degree-4 vertex (4-vertex) origami possesses one continuous degree-of-freedom for rigid folding, and this folding process can be stopped when two of its facets bind together. Such facet-binding will induce so that the overall structure stays at a pre-specified configuration without additional locking elements or actuators. Self-locking offers many promising properties, such as programmable deformation ranges and piecewise stiffness jumps, that could significantly advance many adaptive structural syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 44 publications
0
29
0
1
Order By: Relevance
“…It locks the mountain/valley assignment of certain unit cells, but still allows the pattern to fold smoothly as a rigid origami to the flat-folded states. This is different from motion locking [21] where the panels come into contact with each other hindering the rigid foldability and preventing the pattern from reaching the flat-folded state.…”
Section: (C)(d)) the Bending Poisson's Ratio Is Then Obtained As (Smentioning
confidence: 88%
“…It locks the mountain/valley assignment of certain unit cells, but still allows the pattern to fold smoothly as a rigid origami to the flat-folded states. This is different from motion locking [21] where the panels come into contact with each other hindering the rigid foldability and preventing the pattern from reaching the flat-folded state.…”
Section: (C)(d)) the Bending Poisson's Ratio Is Then Obtained As (Smentioning
confidence: 88%
“…The early study by Schenk and Guest showed that using a nonuniform Miura‐ori crease pattern can ensure that a stacked origami material is locked in a predetermined configuration . Fang et al extended the study by using generic 4‐vertices, and identified several different self‐locking mechanisms that involves facet‐binding either within constituent origami sheets or between adjacent sheets . They further examined the locking‐induced discrete stiffness jumps using both numerical simulations and experiments .…”
Section: Folding Induced Mechanical Propertiesmentioning
confidence: 99%
“…Micro-origami structures like these provide a basic building block for microactuators or metamaterials. [40,41] The Miuraori pattern is well known to have one degree-of-freedom kinematics needed for this actuation approach; however, origami simulation methods such as the rigid folding algorithm [42,43] can be used to determine if other origami patterns also have one degree-of-freedom kinematics. For more complicated patterns, kinematic analysis alone may not be sufficient to determine if the system can be folded accurately and the placement of actuators will play a significant role.…”
Section: Toward Complex Origamimentioning
confidence: 99%